Nueva cita de Guadua tagoara (Poaceae, Bambusoideae, Bambuseae) en la Argentina - Lizarazu, Mabel A. (2012)
Fil: Lizarazu, Mabel A. CONICET. Instituto de Botánica Darwinion [CONICET - ANCEFyN]. San Isidro, Buenos Aires, Argentina.